Theoretical background to the forensic characteristics formation for hostage-taking of a government official or law enforcement officer. (Law and Safety, 2023)
The widespread aggression of the Russian Federation against Ukraine has led to an increase in the number of people in vulnerable situations, including a significant increase in the cases of disappearances and hostage-taking. In this regard, there is a need to improve the methods of investigating the hostage-taking of government officials or law enforcement officers. When developing and formulating an appropriate investigation methodology, it is first of all necessary to determine the forensic characteristics of the relevant crime.The purpose of the article is to define the concept, purpose, sources of formation and elements of the forensic characteristic of hostage-taking of a government official or a law enforcement officer. To achieve this goal, the following methods were used: analysis to work with the existing views of scholars on the issues of forensic characteristics; comparison to summarise information on the seizure of people both in the world and in Ukraine; and the scientific functional method to determine the purpose of forensic characteristics.As a result of the study, it has been established that there are some developments in the formation of various methods for investigating criminal offences, but there is no methodology for investigating the hostage-taking of a government official or a law enforcement officer. Therefore, there is a need, first of all, to formulate a forensic characteristic of the crimes under investigation, which will serve as the first step in the development of the investigation methodology.The concept of “forensic characteristics of hostage-taking of a government official or a law enforcement officer” has been defined as an important component of the forensic methodology, which is a detailed description of a criminal offence which will serve as a basis for solving practical problems arising during the pre-trial investigation. It has been clarified the theoretical and practical role of forensic characteristics, and two types of sources of information necessary for its formation have been identified: persons who have information about a criminal offence, including law enforcement officers, experts and specialists, and other participants to criminal proceedings; as well as relevant documents. Scientific positions on determining the composition of a forensic characteristic have been analysed and typical elements of the forensic characteristic of a hostage taking of a government official or a law enforcement officer have been identified: the circumstances of the crime, the method of its commission, traces of the crime, tools and means, the identity of the victim and the identity of the perpetrator.
Keywords: criminal proceedings; pre-trial investigation; forensic methodology; forensic characteristics; hostage-taking; government official; law enforcement officer.